Potencial delta de Dirac em um cenário de comprimento mínimo - Gusson, Michael França (2016)
Theories that propose the unification of general relativity and quantum mechanics, for example the Quantum Gravity and String Theory, point to the existence of a minimum value of observable length. The existence of this implies a generalization of the Heisenberg’s uncertainty principle, so as to no more admit a null uncertainty in position, thus modifying the algebra of quantum mechanics. This change in algebra suggests a re-evaluation of the results obtained in the usual situations of the quantum context. In this dissertation is discussed the problem of the potential delta d, under the context of a minimum length, and discussed the consequences and results related to this generalization.